Answer:
90%
Step-by-step explanation:
Please give me brainliest :)
Answer:
Step-by-step explanation:
5x - 2 = 55
5x = 57
x = 57/5
Answer:
<h3>9 months</h3>
Step-by-step explanation:
Given the relationship of the dogs weight ang its age modeled by the equation;
w = 6m+4
m represents its age in months, and;
w represents its weight in pounds
Given
w = 58pounds
Required
number of months m before the dog weigh 58pounds;
Substitute w = 58 into the function and get m as shown;
w = 6m + 4
58 = 6m + 4
subtract 4 from both sides
58-4 = 6m+4-4
54 = 6m
divide both sides by 6
54/6 = 6m/6
9 = m
m = 9
Hence it will take 9months before the dog will weigh 58 pounds
Answer:
<h2>Q1. d. 5(x - 4)(x - 6)</h2><h2>Q2. b. (8x - 1)(8x + 1)</h2>
Step-by-step explanation:
![\bold{Q1}\\\\5x^2-50x+120=5(x^2-10x+24)=5(x^2-6x-4x+24)\\\\=5\bigg(x(x-6)-4(x-6)\bigg)=5(x-6)(x-4)\\\\\bold{Q2}\\\\64x^2-1=(8x)^2-1^2=(8x-1)(8x+1)\\\\\text{Used}\ a^2-b^2=(a-b)(a+b)](https://tex.z-dn.net/?f=%5Cbold%7BQ1%7D%5C%5C%5C%5C5x%5E2-50x%2B120%3D5%28x%5E2-10x%2B24%29%3D5%28x%5E2-6x-4x%2B24%29%5C%5C%5C%5C%3D5%5Cbigg%28x%28x-6%29-4%28x-6%29%5Cbigg%29%3D5%28x-6%29%28x-4%29%5C%5C%5C%5C%5Cbold%7BQ2%7D%5C%5C%5C%5C64x%5E2-1%3D%288x%29%5E2-1%5E2%3D%288x-1%29%288x%2B1%29%5C%5C%5C%5C%5Ctext%7BUsed%7D%5C%20a%5E2-b%5E2%3D%28a-b%29%28a%2Bb%29)